Treatment of Parkinson’s Disease by MAO-B Inhibitors, New Therapies and Future Challenges - A Mini-Review - Parambi, Della G.T. (Combinatorial Chemistry & High Throughput Screening, 2020)
Background: One of the most prevalent neurodegenerative diseases with increasing age is Parkinson’s disease (PD). Its pathogenesis is unclear and mainly confined to glutamate toxicity and oxidative stress. The dyskinesia and motor fluctuations and neuroprotective potential are the major concerns which are still unmet in PD therapy. Objective: This article is a capsulization of the role of MAO-B in the treatment of PD, pharmacological properties, safety and efficiency, clinical evidence through random trials, future therapies and challenges. Conclusion: MAO-B inhibitors are well tolerated for the treatment of PD because of their pharmacokinetic properties and neuroprotective action. Rasagiline and selegiline were recommended molecules for early PD and proven safe and provide a modest to significant rise in motor function, delay the use of levodopa and used in early PD. Moreover, safinamide is antiglutamatergic in action. When added to Levodopa, these molecules significantly reduce the offtime with a considerable improvement of non-motor symptoms. This review also discusses the new approaches in therapy like the use of biomarkers, neurorestorative growth factors, gene therapy, neuroimaging, neural transplantation, and nanotechnology. Clinical evidence illustrated that MAOB inhibitors are recommended as monotherapy and added on therapy to levodopa. A large study and further evidence are required in the field of future therapies to unwind the complexity of the disease.
Keywords: MAO-B inhibitors